Pattern injuries from blows with the muzzle end of a handgun. (December 2015) - Geisenberger, D.; Vogt, S.; Pircher, R.; Kramer, L.; Pollak, S.; Große Perdekamp, M.
Abstract: Pistols, revolvers and blank guns are not only used to discharge cartridges, but also for hits to the victim. In such cases, the blows preferably affect the head and/or the interposed hands protecting the body. The impact is mostly exerted either by the grip of a pistol or the butt of a revolver. In vigorous thrusts inflicted with the muzzle end of the weapon, the edge of the barrel may produce circular punch lesions with central skin flaps roughly corresponding to the bore. As in other kinds of pistol-whipping, the scalp wounds may be associated with fractures of the skull and even with brain contusions. Using the example of a homicide committed by pistol-whipping, the morphological features of blunt injuries from a handgun's muzzle are presented. The characteristic wound pattern found on the victim's head could be reproduced experimentally by forceful blows to the forehead of a slaughtered pig. In the case presented, the dominant hand of the perpetrator showed friction blisters due to prolonged striking with an unhandy tool in the form of a pistol.